"THE STATE and MIGRATION IN CHINESE HISTORY". Issue 2 (July 2021) - Barbieri-Low, Anthony J.
Abstract: This special issue of the Journal of Chinese History is dedicated to studies of the connection between migration and the state throughout Chinese history. The special editor's introduction first surveys the major types of migration within China proper, and towards the outside world, including citations to recent scholarship. It brings the eight papers of this issue into dialogue with each other around four major themes: migration and the limits of state power, the violence and trauma of migration, migration and identity, and migration and gender/family issues.